(untitled) (Journal of Medical & Health Sciences Review, 2025)
In recent years, there has been a lot of interest in the creation of environmentally benign and biocompatible nanomaterials for use in biomedicine. Azadirachta indica (neem) leaf extract is used in this study’s environmentally friendly biosynthesis of iron oxide nanoparticles (IONPs), with the goal of utilizing them for targeted cancer imaging and treatment. By using the phytochemicals found in neem extract as stabilizing and reducing agents, the green synthesis method does not require hazardous chemicals. When UV-Vis spectroscopy was used to characterize the synthesized nanoparticles, it showed a distinctive absorption peak at 241.83 nm, confirming the formation of the nanoparticles. Functional groups like hydroxyl, carbonyl, and amide were detected by FTIR analysis, confirming the role of neem phytochemicals in stabilizing and protecting the nanoparticles. The successful synthesis of FeO₄ nanoparticles was confirmed by the iron–oxygen bond signatures in the FTIR and unique morphological features in the SEM. By reducing the negative effects on the environment and improving biocompatibility, this green method provides a sustainable substitute for the synthesis of nanoparticles. The biosynthesized IONPs show promising potential for use in targeted drug delivery, magnetic hyperthermia in cancer treatment, and magnetic resonance imaging (MRI) due to their nanoscale size, magnetic characteristics, and organic surface coating. For safe and efficient application in cancer theranostics, this work defines a basis for additional functionalization and in vitro/in vivo evaluation of green-synthesised iron oxide nanoparticles.